Analysing The Quality Attributes of AOP using CYVIS Tool - Garg, Hinam; Garg, Mohit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
The aim of thesis is to provide the difference between AOP and OOP in AspectJ by using CYVIS tool. It gives a way to separate the code from essential crosscutting concerns, such as logging and security, from Java programs core application logic cleanly by making code more readable, less error-prone, and easier to maintain. It also solves the problem of code scattering and code tangling by providing the aspect to crosscutting concerns (concerns which are repeated again and again). In this paper, aspect oriented programming is shownÂ  better than OOP by considering cyclomatic complexity Â and overcoming all those problems which were occurring in OOP. Two examples such as banking system and conversion of int and float values to hexadecimal are illustrated and shows the difference of quality attributes in AOP than OOP.